Asumsi Terhadap Manusia Sebagai Individu Dalam Pengembangan Organisasi Di SD N 05 Air Tawar Barat, Kota Padang - Bayu Putra Niami (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study aims to analyze the assumptions about human beings as individuals within the context of organizational development at SDN 05 Air Tawar Barat, Padang City. The research focuses on understanding human perspectives as rational, social, and developing beings through the role of educational organizations. The study employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The data were analyzed using thematic analysis to identify behavioral patterns, attitudes, and values that reflect assumptions about individuals within the school organization. The results reveal that teachers and school leaders hold a positive view of individuals as the main assets of the organization. This assumption is manifested through the provision of space for creativity, professional development, and active participation in decision-making. The findings highlight that effective organizational development must be grounded in respect for human potential as unique and dynamic individuals.